ANALYSIS OF LECTURERS' PROFESSIONALITY TOWARDS PRE- SERVICE TEACHERS' PROFESSIONAL COMMITMENT (CAPACITY BUILDING OF TEACHER TRAINING AND EDUCATION FACULTY) - Ratnawati Susanto (Universitas Muhammadiyah Ponorogo, 2018)
Institutes of Teacher's Education (LPTK) requires to develop some steps to strengthen its internal capacity through lecturer professionalism in shaping professional commitment. Research is needed to create creative and futuristic strategies to overcome the problems: (1) the professionalism of pre-service teacher graduates is still low, (2) Institutes of Teacher's Education have not meet the standard, (3) pre-service teachers have not been professional. The research was conducted in teacher training and education faculty and the subjects were 161 active students (saturated sampling). Survey method was applied with causal analysis and questionnaire as data collection instrument. Result showed that (1) lecturers were quite professional, (2 pre-service teachers had high commitment to their profession, (4) it had a positive, strong and very significant effect between professional lecturer and commitment to their profession. The research recommends: (1) improving the capacity of lecturers' professionalism, (2) optimizing students' perceptions on professional lecturers, (3) involving parent roles and related research, (4) developing the lecturer professional and research planning (RIP) policy on learning and academic culture in in Institutes of Teacher's Education